Richard III : the self-made king - Hicks, Michael, 1948- (Yale University Press, 2019)
The definitive biography and assessment of the wily and formidable prince who unexpectedly became monarch--the most infamous king in British history.
Keywords: Richard -- III, -- King of England, -- 1452-1485.; Richard -- III, -- King of England, -- 1452-1485; Richard -- III. -- England, König -- 1452-1485; Great Britain -- Kings and rulers -- Biography.; Great Britain -- History -- Richard III, 1483-1485.; Grande-Bretagne -- Histoire -- 1483-1485 (Richard III); Biography.; Kings and rulers; Great Britain; 1483-1485; Biography; Biographies; History; Biographies.